Studies on the Aviation Industry Based on Industrial Organization - Dong, Chang (Université d'Ottawa | University of Ottawa, 2024)
This paper uses data from the 2000 to 2019 U.S. civil aviation industry to analyze the disparities in jet fuel cost pass-through among legacy, low-cost, and ultra-low-cost carriers. Different pricing mechanisms are determined by different business structures. We use empirical methods to study which category of carriers transfers more of the cost increase to final consumers when facing an increase in jet fuel costs. According to the findings, when faced with an increase in jet fuel costs, low-cost carriers are more likely than legacy carriers to increase flight ticket prices. Compared to legacy and low-cost carriers, ultra-low-cost carriers have the lowest pass-through. This paper uses the financial data analysis and event study approach to evaluate the market performance and financial performance of legacy carriers and low-cost carriers in China and the U.S. during the COVID-19 pandemic. Analysis of financial reports and ratios reveals that legacy carriers in both countries experience a greater revenue loss than low-cost carriers, while low-cost carriers keep more liquidity and better loan repayment capability during the pandemic. The cumulative average abnormal returns and average buy-and-hold abnormal returns to publicly traded airline stocks in the U.S. are significantly higher than those in China, both in the short-term and long-term event windows. In the short run, both Chinese and U.S. legacy carriers are more affected than low-cost carriers. State ownership has not significantly helped China's airline stocks mitigate negative shocks. This paper examines the evolution of airfare ticket prices following the merger of the market with and without low-cost carriers. Using demand estimation and merger simulation methods, we examine how the presence of low-cost airlines in mergers influences the post-merger price through four mergers in the U.S. airline industry in the late 2000s and early 2010s. Our analysis reveals that the post-merger ticket increase is notably less pronounced in markets where low-cost airlines operate as opposed to markets without low-cost carriers. This suggests that low-cost carriers generate considerable competitive pressure, effectively limiting the ability of merged entities to raise prices and thereby protecting consumer welfare.
Keywords: Aviation industry; Cost pass-through; Legacy carrier; Low-cost carriers; Fuel costs; COVID-19; Merger and acquisition